2020
DOI: 10.3390/ijerph17103680
|View full text |Cite|
|
Sign up to set email alerts
|

The Benefits of Physical Exercise on Mental Disorders and Quality of Life in Substance Use Disorders Patients. Systematic Review and Meta-Analysis

Abstract: Physical exercise seems to have a promising effect on numerous variables related to the recovery of drug-dependent patients. However, some contradictions are found in the literature. The aim of this study was to perform a systematic review and meta-analysis in order to identify the effect of physical exercise on mental disorders, quality of life, abstinence, and craving, and make a comparison of the effect of exercise depending on the type of program. A search for articles was conducted using PubMed, Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 85 publications
(386 reference statements)
2
60
0
1
Order By: Relevance
“…Several studies have shown that mental state disorders are associated with an increased risk of low QoL in physical, psychological, and social domains [ 28 ]. Therefore, mental state disorders have been associated with significant impairment in QoL [ 27 , 29 ]. Accordingly, it is necessary to conduct an analytical study including a case group (women with substance use disorder) and a control group (healthy women).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that mental state disorders are associated with an increased risk of low QoL in physical, psychological, and social domains [ 28 ]. Therefore, mental state disorders have been associated with significant impairment in QoL [ 27 , 29 ]. Accordingly, it is necessary to conduct an analytical study including a case group (women with substance use disorder) and a control group (healthy women).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that mental state disorders are associated with an increased risk of low QoL in physical, psychological, and social domains (28). Therefore, mental state disorders have been associated with signi cant impairment in QoL (27,29). Accordingly, it is necessary to conduct an analytical study including a case group (women with substance use disorder) and a control group (healthy women).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that mental state disorders were associated with an increased risk of low quality of life in physical, psychological, social domains (27). Therefore, mental state disorders have been associated with signi cant impairment in quality of life (26,28). So, it seems that the analytical study includes a case group (substance abuse disorder women), and a control group (healthy women) was essential.…”
Section: Discussionmentioning
confidence: 99%